2023
DOI: 10.1128/spectrum.00393-23
|View full text |Cite
|
Sign up to set email alerts
|

Erg6 Acts as a Downstream Effector of the Transcription Factor Flo8 To Regulate Biofilm Formation in Candida albicans

Abstract: Biofilm formation by C. albicans hinders its eradication by immune cells and antifungal drugs. Flo8 is an important morphogenetic transcription factor that regulates the biofilm formation and in vivo virulence of C. albicans .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…However, erg6 loss-of-function mutations in these organisms cause alteration of drug susceptibility and defective growth phenotypes related to membrane integrity and permeability. Recent exciting studies have shown that loss of C. albicans Erg6 activity, either through genetic downregulation of ERG6 gene transcription or through pharmacologic inhibition of Erg6 protein activity with a novel small molecule, blocks the pathogenic yeast-to-hyphae transition and significantly reduces virulence 19 , 20 . Studies of Erg6 in filamentous fungi are relatively very limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, erg6 loss-of-function mutations in these organisms cause alteration of drug susceptibility and defective growth phenotypes related to membrane integrity and permeability. Recent exciting studies have shown that loss of C. albicans Erg6 activity, either through genetic downregulation of ERG6 gene transcription or through pharmacologic inhibition of Erg6 protein activity with a novel small molecule, blocks the pathogenic yeast-to-hyphae transition and significantly reduces virulence 19 , 20 . Studies of Erg6 in filamentous fungi are relatively very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The pGADT7 and pHIS2 plasmids were employed for yeast one-hybrid assay [ 25 ]. The HOF1 promoter, in different lengths, was amplified by PCR and inserted into the EcoR I site of the pHIS2 plasmid as bait using the Universal One Step Cloning Kit (Yeasen, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…G. mellonella has been used to study many fungi, including Aspergillus spp., Candida spp., Cryptococcus spp., Conidiobolus coronatus , Histoplasma capsulatum , Madurella mycetomatis , Malassezia spp. and Paraccocidioides brasiliensis [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: G Mellonella As a Model To Study Fungi In Vivomentioning
confidence: 99%
“…Categorising studies using G. mellonella larvae to assess virulence or drug efficacy is a challenging task. It is more appropriate to evaluate the work based on different fungal genera since some species have undergone extensive research in recent years [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: G Mellonella As a Model To Study Fungi In Vivomentioning
confidence: 99%
See 1 more Smart Citation